2018
DOI: 10.1002/smtd.201800182
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Enhanced Raman Nanoprobes with Embedded Standards for Quantitative Cholesterol Detection

Abstract: Cholesterol is an essential molecule for many processes in the human body and many diseases such as hypertension, coronary heart disease, atherosclerosis, and lipid metabolism dysfunction can be detected in their early stages by monitoring intracellular cholesterol levels. Herein, metallic surface‐enhanced Raman scattering (SERS) core–shell nanoparticles with an embedded standard are designed for nondestructive detection of H2O2 and cholesterol. A classical least squares (CLS) spectral fitting method allows on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 93 publications
2
50
0
Order By: Relevance
“…Most of the previous research has focused on the heterogeneous nucleation and growth of Au or Ag layer on a single particle system in which surface ligands and lattice misfit affect the interfacial energy between seed and growing layer, [ 27,34,38,39,45 ] however, we found out that the Ag growth on the facet‐blocked Au NPs assembled Fe 3 O 4 NPs occurred as the 3D island growth with the one‐sided direction. There is a possibility that since an Ag island has a lower interfacial area with the facet‐blocked Au NPs than many Ag islands the free energy during the Ag growth could be minimized by decreasing the interfacial energy between MP templates and Ag islands.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Most of the previous research has focused on the heterogeneous nucleation and growth of Au or Ag layer on a single particle system in which surface ligands and lattice misfit affect the interfacial energy between seed and growing layer, [ 27,34,38,39,45 ] however, we found out that the Ag growth on the facet‐blocked Au NPs assembled Fe 3 O 4 NPs occurred as the 3D island growth with the one‐sided direction. There is a possibility that since an Ag island has a lower interfacial area with the facet‐blocked Au NPs than many Ag islands the free energy during the Ag growth could be minimized by decreasing the interfacial energy between MP templates and Ag islands.…”
Section: Resultsmentioning
confidence: 78%
“…It was previously reported that BDT molecules suppress the deposition of Ag atoms but not Au atoms during the seed‐mediated growth of Au NPs. [ 45 ] Thus, uniform Ag deposition on BDT‐modified Au NPs is energetically unfavorable for layer‐by‐layer growth. However, we confirmed that Ag islands resulted in an Au facet‐blocked environment with different ligands, such as 4‐aminophenol (ATP) and 4‐mercaptobenzoic acid (MBA) (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…SERS nanoparticles can be utilized as optical labelling nanoprobes, similar to uorescent dyes and quantum dots, for bioimaging and biosensing with the additional advantages of ngerprint vibrational signals as a unique optical code and ultra-narrow line widths for multiplexing. 22,56,57 Typically, SERS efficiencies reach maximal values at resonant conditions, i.e., when the excitation wavelength overlaps with the LSPR wavelength, preferably in the near-infrared (NIR) biological window. However, on-resonant photogenerated heat may inevitably disturb or even destroy a biological sample or induce photobleaching of the SERS signals during the imaging process.…”
Section: Maldi Ms and Sers Based Diagnosticsmentioning
confidence: 99%
“…As a consequence of tunable LSPR and photothermal effects, AuNR has been used in different biomedical applications . Mesoporous silica or polymers are commonly modified on the surface of AuNR to reduce clustering and aggregation . Nevertheless, these substances tend to separate from AuNR, resulting in poor stability and potential toxicity .…”
Section: Applications Of Graphitic Nanocapsulesmentioning
confidence: 99%